THE MEANING OF REGRET AND LIFE VALUES IN MENYESAL BY ALI HASJMY: AN ANALYSIS OF ROLAND BARTHES' FIVE SEMIOTIC CODES - Anisa Suciani; Iis Halisa; Bambang Riadi (Wiyata Budaya: Jurnal Pendidikan Dalam Konteks Humaniora, 2026)
Previous studies on the poem Menyesal by Ali Hasjmy have primarily focused on its intrinsic elements and moral messages. However, comprehensive studies employing Roland Barthes' five semiotic codes to reveal the multilayered meanings embedded in the poem remain limited. Therefore, this study aims to analyze the meanings of Menyesal through Barthes' five semiotic codes, namely the actional code, hermeneutic code, cultural code, connotative code, and symbolic code. This research employed a qualitative descriptive method using Roland Barthes' semiotic approach. The data consisted of the verses of the poem Menyesal, which were collected through close reading and note-taking techniques and analyzed using the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the poem embodies Barthes' five semiotic codes, which collectively construct its overall meaning. The actional code portrays the lyrical subject's negligence in making productive use of youth, ultimately leading to regret. The hermeneutic code presents interpretative questions concerning the causes and consequences of life choices. The cultural code reflects social values emphasizing the importance of education, hard work, responsibility, and dedication to society. Furthermore, the connotative code assigns deeper meanings to symbols such as morning, evening, knowledge, and wealth, while the symbolic code establishes binary oppositions between youth and old age, hope and regret, as well as productivity and passivity. These findings demonstrate that the poem conveys not only the poet's personal experience but also universal moral reflections on the importance of valuing time and making meaningful life choices. This study concludes that Roland Barthes' semiotic framework effectively reveals the multiple layers of meaning embedded in the poem through the interrelationship of the five semiotic codes. The analysis demonstrates that Menyesal presents philosophical reflections on life, regret, responsibility, and self-devotion that remain relevant to contemporary society. Therefore, this study contributes to the development of Indonesian literary semiotics and provides a valuable reference for future research on semiotic analyses of literary works.